Evolution of Low Mass Contact Binaries - Stępień, K.; Gazeas, K. (2012)
VFTS 682, a very massive and very hot Wolf-Rayet (WR) star recently discovered in the Large Magellanic Cloud near the famous star cluster R136, might be providing us with a glimpse of a missing link in our understanding of Long Gamma-Ray Bursts (LGRBs), including dark GRBs. It is likely its properties result from chemically homogeneous evolution (CHE), believed to be a key process for a massive star to become a GRB. It is also heavily obscured by dust extinction, which could make it a dark GRB upon explosion. Using Spitzer data we investigate the properties of interstellar dust in the vicinity of R136, and argue that its high obscuration is not unusual for its environment and that it could indeed be a slow runaway (``walkaway'') from R136. Unfortunately, based on its current mass loss rate, VFTS 682 is unlikely to become a GRB, because it will lose too much angular momentum at its death. If it were to become a GRB, it probably would also not be dark, either escaping or destroying its surrounding dusty region. Nevertheless, it is a very interesting star, deserving further studies, and being one of only three presently identified WR stars (two others in the Small Magellanic Cloud) that seems to be undergoing CHE.
Keywords: Astrophysics - Solar and Stellar Astrophysics; binaries: close; binaries: eclipsing; Planets and satellites: formation; stars: evolution; Stars: low-mass